ESTIMATION OF GROUNDWATER POTENTIAL OF PENAJAM REGION TO SUPPORT THE NEED FOR CLEAN WATER IN IKN PENAJAM EAST KALIMANTAN - Arie Herlambang Soeseno (Jurnal Sains dan Teknologi Mitigasi Bencana, 2022)
Ground water is a source of water that can be used to support the clean water needs of the certain area.Water sources can be from springs or pumping from shallow (<40 meters) or deep (generally> 40 metersto 200 meters) depths groundwater. The geological conditions of an area determine the location, area ofdistribution and the position and composition of the rock that acts as an aquifer. As an initial identificationof shallow groundwater, it can be done from resident wells in the study area, while for groundwaterinformation is obtained from drilling that has been carried out in the study area, especially information onpumping tests that have been carried out. Low groundwater potential is found in the western part and partlyin the center of the IKN area. Shallow groundwater is found at a depth of 20 meters (below ground level,bmt), groundwater levels can be found at a depth of 5.3 m (bmt), permeability (K) is around 0.03048 m /day, with transmissivity (T) around 11.14836 m2 / days, with optimal discharge (Qopt) 0.1183 liters / secondat a distance between wells (2R) 78.4 m and with a good water quality. Depressed groundwater can befound at a depth of 32 - 117 m bmt, with a static groundwater level of 9.25 - 28 m bmt, permeability 0.0064- 0.4572 m / day, transmissivity (T) ranging from 0.2508 to 20,4387 m2 / day, optimal flow rate 0.1183 -0.9077 l / second, with between wells 87.19 - 170.07 m, with a good water quality. The area of the IKNcandidate location itself is in a plains area, which is dominated by moderate potential aquifers, with aquiferdepths ranging from 150 - 350 m, groundwater levels of 1 - 4 m below ground level, permeability (K) rangingfrom 9.6 x 10-6 - 1.1 x 10-5 cm / second, and transmissivity (T) 0.003 - 0.004 m2 / day, the optimal dischargeis 10.8 - 27.5 liters / second. Potential areas for IKN locations with high potential aquifers, located in thesouth of the IKN area, especially towards the coast, are found at a depth below ground level of 150 - 350meters, groundwater level 1 - 4 m, permeability (K) ranges from 9.6 x 10 -6 - 1.1 x 10-5 cm / second, andtransmissivity (T) 0.003 - 0.004 m2 / day, the optimal discharge is 10.8 - 27.5 liters / second.